Returning to the land concentration in Perú - Arias Nieto, Custodio (2012)
In this article I present the new process of land concentration in Peru that has been taking place in the last fifteen years in the context of the laws generated inside the neoliberal model. These laws have allowed the emergency of the latifundium in the most fertile lands of the peruvian coast. Its production is mainly for export. Similarly mining concesions, oil and forestry are generating a new type of land concentration, degrading or destroying this resource together with the existing biodiversity. Finally,the prior consent of indigenous communities established in the Convention 169 ILO signed by the Peruvian state is not been respected as the land in their territories is being handed over as concessions.